PELAYANAN PUBLIK PASCA PEMEKARAN WILAYAH DI UPTD DISDUKCAPIL KECAMATAN TAMPAN KOTA PEKANBARU - ", Wilingga; Rusli SD, Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Pekanbaru City implemented regional expansion in 2017. Through the Regional Regulation of Pekanbaru City Number 4 in 2016, there were 25 additional villages from seven sub-districts. One of the goals of regional expansion is to maximize public services for the community. The problem: first, The human resources owned by the UPTD are not optimal. Second, Facilities and infrastructure are poor. The purpose of this study was to analyze public services after the expansion of the area in Tampan District, Pekanbaru City. The location of this research is in Tampan District. Research uses theory (Makmur & Thoha, 2017) which consists of tangible, realibility, responsivennes, assurance and empathy. The research method used is qualitative with a descriptive approach. The results of this study indicate that the public has not been satisfied with the performance of public services after regional expansion. Inadequate facilities and infrastructure, a long processing time, many inappropriate service products. In addition, there are also uncomfortable seats, inadequate chairs provided. So people who are waiting in line donâ€™t get good comfort. The service officers at UPTD Tampan Subdistrict, Pekanbaru City have not been able to provide quality services for people who need public services. Plus, administrative staff are still lacking in good human resources. Keywords: Public Services, Regional Expansion, Regional Technical and Civil Registration Service Units.Â Â